If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 13 = -20 + 7x Reorder the terms: 13 + 4x = -20 + 7x Solving 13 + 4x = -20 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 13 + 4x + -7x = -20 + 7x + -7x Combine like terms: 4x + -7x = -3x 13 + -3x = -20 + 7x + -7x Combine like terms: 7x + -7x = 0 13 + -3x = -20 + 0 13 + -3x = -20 Add '-13' to each side of the equation. 13 + -13 + -3x = -20 + -13 Combine like terms: 13 + -13 = 0 0 + -3x = -20 + -13 -3x = -20 + -13 Combine like terms: -20 + -13 = -33 -3x = -33 Divide each side by '-3'. x = 11 Simplifying x = 11
| 2x+11=-19+4x | | 7x+9=-21+x | | 5-2x=8-3x | | 2x-5=8-3x | | 37=-3+5(u+6) | | 0=x^4-2x^2 | | h(t)=-16t^2+4.8768t+19.812 | | t^2+7t+30=0 | | 57*x^2-14*x^3-16=0 | | 5x-(4*-3x+5)=-3 | | (x^2)/1.66-x=0.497 | | (x^2)/1.66-x=0 | | -2x-3*6x-11=-7 | | 259=-6x+19 | | 5m-9=26 | | -18-6e=6(1+3e) | | (7/3b)3 | | 6/a=4/3 | | 5x-2x^2+3x+4x^2= | | -6x+9+7x=15-31 | | -6(1+5m)=54 | | 5000/.84 | | 5000*/0.84 | | 84=12*(X) | | 5x+2x^2+3x-4x^2= | | 7x-2*2=10 | | 5x+2x^3-9x-8x^3= | | -6(1+5l)=54 | | 4x^2+6x=y-2 | | 3p-5=(p-1)(p-2) | | (x+4)(x+4)-14=0 | | 7x/35=4x-5/6 |